Studiul rolului diverșilor factori patogeni în dezvoltarea aritmiilor și a hemodinamicii centrale afectate la pacienții cu tuberculoză pulmonară cu diabet zaharat concomitent. - Зейнаб Курбанова (Academy of Sciences of Moldova, 2019)
Study of the role of various pathogentic factors in the devolpment of arhythmias and central hemodynamic disordes in patients with pulmonary tubeculosis and diabets mellities